Protection of minority rights and diversity - South Asian Conference on Diversity (2000 : Colombo, Sri Lanka); Wanasundera, Nanda P. (Nanda Pethiyagoda), 1932-; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 2004)
Contributed articles presented at the South Asain Conference on Diversity held at Colombo on Nov. 16-18, 2000.
Keywords: Minorities -- Civil rights -- Sri Lanka; Ethnic groups -- Civil rights -- Sri Lanka; Representative government and representation -- Sri Lanka; Multiculturalism -- Sri Lanka